Lower limb strength training in children with cerebral palsy - a randomized controlled trial protocol for functional strength training based on progressive resistance exercise principles - Verschuren Olaf; Rameckers Eugene A; Dallmeijer Annet J; Scholtes Vanessa A; Tempelaars Els; Hensen Maartje; Becher Jules G (BMC, 2008)
Abstract Background Until recently, strength training in children with cerebral palsy (CP) was considered to be inappropriate, because it could lead to increased spasticity or abnormal movement patterns. However, the results of recent studies suggest that progressive strength training can lead to increased strength and improved function, but low methodological quality and incomplete reporting on the training protocols hampers adequate interpretation of the results. This paper describes the design and training protocol of a randomized controlled trial to assess the effects of a school-based progressive functional strength training program for children with CP. Methods/Results Fifty-one children with Gross Motor Function Classification Systems levels I to III, aged of 6 to 13 years, were recruited. Using stratified randomization, each child was assigned to an intervention group (strength training) or a control group (usual care). The strength training was given in groups of 4-5 children, 3 times a week, for a period of 12 weeks. Each training session focussed on four exercises out of a 5-exercise circuit. The training load was gradually increased based on the child's maximum level of strength, as determined by the 8 Repetition Maximum (8 RM). To evaluate the effectiveness of the training, all children were evaluated before, during, directly after, and 6 weeks after the intervention period. Primary outcomes in this study were gross motor function (measured with the Gross Motor Function Measure and functional muscle strength tests) and walking ability (measured with the 10-meter, the 1-minute and the timed stair test). Secondary outcomes were lower limb muscle strength (measured with a 6 RM test, isometric strength tests, and a sprint capacity test), mobility (measured with a mobility questionnaire), and sport activities (measured with the Children's Assessment of Participation and Enjoyment). Spasticity and range of motion were assessed to evaluate any adverse events. Conclusion Randomized clinical trials are considered to present the highest level of evidence. Nevertheless, it is of utmost importance to report on the design, the applied evaluation methods, and all elements of the intervention, to ensure adequate interpretation of the results and to facilitate implementation of the intervention in clinical practice if the results are positive. Trial Registration Trial Register NTR1403